Cartilla de análisis de arcos metálicos en túneles y ábacos de diseño (2015)
The directed work, called "Metallic arc analysis book in tunnels and design abacuses"; consists in the design of a tool with which through the conjugation of variables evaluated by means of modeling with the finite element software SAP 2000, facilitate, speed up the design process of metal arches in tunnels and constitute a method for the design of metal arcs intermediate between an empirical design and one of detail from the implementation of finite element programs. Although commutations of the variables such as the Poisson's ratio or the modulus of elasticity of the massif were not taken into account, in order to limit the amount of modeling, an attempt was made to create the abacuses from the most relevant conditions, in order to obtain a practical and reliable tool. In order to check the functionality of the abacuses, Colombian case studies were taken as reference, which present metallic arcs of smaller specifications compared with those suggested by some of the empirical methods, and which have worked satisfactorily. Being able to establish that the abacus are applicable and work satisfactorily to offer less conservative results, with respect to the empirical and therefore more efficient.